Odpowiedzi

2009-11-12T18:24:06+01:00
72⁰ * 3¹ -(√5-3)(√5+3)+2⁻¹ *√64 =
1*3 -5+9+½ *8=3+4+4=11
2009-11-12T18:27:51+01:00
72⁰ * 3¹ -(√5-3)(√5+3)+2⁻¹ *√64 =3-(√5²-(3²))+1/2*8=3-(5-9)+4=3-(-4)+4=3+4+4=11
Najlepsza Odpowiedź!
2009-11-12T18:39:50+01:00
72⁰ * 3¹ -(√5-3)(√5+3)+2⁻¹ *√64 = 1*3-5+9+½*8=3-5+9+4 = 11
0,1*11=9,9

√5i 4/9 +2⁻¹ / (2:√4⁻¹) *(1/2)²+ 1/6 = √49/9+½ / (2:½)*¼+⅙ = 7/3+½/4*¼+⅙ = 7/3+½/1+⅙ = 7/3+½+⅙ = 14/6+3/6+1/6 = 18/6 = 3
0,1*3=0,3

2-(-1½)²*√0,04+(√2/2)² / (1-1 i 1/2)² * ∛8 = 2-2,25*0,2 / -¼*2 = 2-0,45/-0,5 = 2+0,9 = 2,9
0,1*2,9 = 0,29